Benzyl Nicotinate as an Efficient Corrosion Inhibitor for Cold Rolled Steel in a 1 M HCl Solution - Vinutha,M. R. (2017)
The ability of benzyl nicotinate (BN) to inhibit the corrosion process of cold rolled steel (CRS) in a 1 M HCl solution has been investigated by weight loss measurements, potentiodynamic polarization and electrochemical impedance spectroscopic methods. The potentiodynamic polarization study revealed that BN acts as a mixed type inhibitor. The effect of temperature range (303-333 K) on the corrosion of steel was studied at different concentrations of BN. The efficiency of this inhibitor increases with an increase in its concentration, and decreases with rise of temperature. Free energy values revealed that BN molecule undergoes comprehensive adsorption. The adsorptive behavior of BN on CRS obeys Langmuir adsorption. The thermodynamic and activation parameters calculation helped in getting insight into the inhibitor mechanism. The DFT (density functional theory) studies of BN molecule also supported our experimental findings.